The Influence of Financial Literacy, Locus of Control, Income, and Education Level on Retirement Planning of Elementary School’s Teachers with Civil Servant Status in the City of Surabaya - Saputri, Sahrin Fifit Dwi (CV ODIS, 2021)
Retirement fund planning is an important thing of employee life including for individuals who work in the government environment considering that until now the structure of civil servants especially teachers is dominated by the age of 40 and above. The main objective of this current study is to examine the factors that influence individual behavior in perencanaan dana pensiun behavior. The four factors had been considered to these research are financial literacy, locus of control, income and education level. A total of 98 respondents who are primary school teachers with civil servant status in Surabaya have participated on this study. Online questionnaires are used to collect data that have been tested for validity and reliability first. All data in this study are analyzed using SPSS. Overall, the results of this research revealed that financial literacy and locus of control were supported however intriguing findings for income and education level were not supported.